Enhancing Ethical Sensitivity and Decision Making Through Accounting Ethics Education Based on Islam - muslichah muslichah (STIE Malangkucecwara, 2022)
This paper examines the effectivenes of Accounting Ethics Education Based on Islam (AEEBI) by comparing a level of ethical sensitivity and ethical decisionmaking of Muslim accounting students. Using a pre and post survey, this study examine ethical sensitivity and ethical decision-making of Muslim students who have undertaken AEEBI lecture. This study used a survey questionnaire to collect data from five selected universities (three public universities and two private universities). The number of Muslim accounting students who participated in this study was 202 students. There are two significant findings of this study. First, there are differences in ethical sensitivity and ethical decision making before and after Muslim accounting students attend AEEBI lectures. After attending AEEBI lectures, the ethical sensitivity and decision making of Muslim students has increased.